Analisis dampak imperialisme dan kolonialisme belanda terhadap struktur sosial dan ekonomi Indonesia - sobih, muhammad (Maliki Interdisciplinary Journal, 2025)
This article discusses the forms of imperialism and colonialism practiced by the Dutch in Indonesia and their impact on the social structure of society. Dutch colonialism took place in various phases, starting from the arrival of the VOC as an instrument of economic colonialism based on the monopoly of the spice trade, to the transition to political and administrative colonialism after the VOC was dissolved. In the later phase, policies such as the Cultivation System (Cultuurstelsel) and Ethical Politics reflected the transformation of colonial methods that became more systematic and entrenched. Based on Hobson and Lenin's theory of imperialism, Dutch colonialism in Indonesia was part of a global capitalist strategy to access markets, raw materials and investment. It also had a major structural impact on Indonesian society, including the creation of new social classes, racial discrimination and sharp social stratification. This article highlights how the process of colonialism not only exploited natural resources and labor, but also profoundly changed the social and cultural fabric of Indonesian society.